Analisis Perbedaan Sekuen 3D DIR pada MRI Brain Kasus Epilepsi (Studi Komparasi 3D T2 FLAIR SPACE) di Instalasi Radiologi RSUP Prof. Dr. I.G.N.G. Ngoerah - Evhal Yulianus; I Made Lana Prasetya; Triningsih Triningsih (Poltekkes Kemenkes Semarang, 2024)
Background: Double Inversion Recovery (DIR) is a newer sequence compared to the T2 FLAIR sequence in MRI Brain examinations used for epilepsy cases. Further research is needed to determine the optimal sequence for MRI Brain in epilepsy cases.Methods: This research is a quantitative study with an experimental approach. This study uses DIR and T2 SPACE sekuen to assess image quality in terms of Contrast to Noise Ratio (CNR). The data will be analyzed using SPSS.Results: The normality test shows a p-value 0.05, indicating that the data is not normally distributed. In the Wilcoxon test, the negative rank indicates a decrease in image quality (CNR) from the DIR sequence to T2 FLAIR SPACE. The test statistics show a p-value 0.05, indicating a significant difference in image quality (CNR) between the DIR and T2 FLAIR SPACE sekuen.Conclusions: The Contrast to Noise Ratio (CNR) image quality in Double Inversion Recovery (DIR) is higher compared to T2 FLAIR SPACE, thus making the DIR sequence more optimal in assessing image quality (CNR) compared to the T2 FLAIR SPACE sequence.